Chemical composition and digestibility of Amaranthus dubius Mart. ex Thell. A promisingsource of nutrients - Montero, K.; Moreno, R.; Molina, E.; González, P.; Sánchez, A. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2015)
The chemical Â composition and digestibility of leaves, stems and panicles of Amaranthusdubius Mart. ex Thell. were evaluated. We collected the samples in Merecure, estado Miranda, Venezuela, in two collecting seasons (rainy and dry). We determined the proximate composition, dietetic fiber, acid detergent fiber, neutral detergent fiber, lignin and digestibility of the organic matter and of the neutral detergent fiber. We observed the interaction among these factors in most of these analyses, except for the crude fiber and neutral detergent fiber. The highest content of protein (270.90 g.kg-1 ), ashes (211.70 g.kg ) and the highest digestibility of the organic matter (910.80 g.kg-1-1) and of the neutral detergent fiber (770.50 g.kg ) were found in leaves during the rainy season. Protein concentration was lowerin the stems during the dry season (60.80 g.kg-1), and the lowest ether extract content (3.60 g.kg ) and lower digestibility of the organic matter (469.90 g.kg-1-1 ) were found in the stems during the rainy season. The panicle presented the highest ether extract (22.40 g.kg-1 ) and lignin (190.90 g.kg ) contents. The organ of the plant and the collecting season both affect the proximate composition and fiber content of A. dubius. Because of its high nutritional value and digestibility, it has potential as a food and feed supplements.